Molecular Mechanisms Underlying Bacterial Uranium Resistance - Rogiers, Tom; Van Houdt, Rob; Williamson, Adam; Leys, Natalie; Boon, Nico; Mijnendonckx, Kristel (Frontiers in Microbiology, 2022)
Environmental uranium pollution due to industries producing natural occurring radioactive material or nuclear accidents and releases is a global concern. It is hazardous for ecosystems as well as for humans when accumulated through the food chain, through contaminated groundwater and potable water sources, or through inhalation. In particular, uranium pollution pressures microbial communities, which are essential for healthy ecosystems. In turn, microorganisms can influence the mobility and toxicity of uranium through processes like biosorption, bioreduction, biomineralization and bioaccumulation. These processes were characterized by studying the interaction of different bacteria with uranium. However, most studies unravelling the underlying molecular mechanisms originate from the last decade. Molecular mechanisms help to understand how bacteria interact with radionuclides in the environment. Furthermore, knowledge on these underlying mechanisms could be exploited to improve bioremediation technologies. Here, we review the current knowledge on bacterial uranium resistance and how this could be used for bioremediation applications.